Tổng hợp các dẫn xuất pyrolizin mới - Phong Lan, Phạm Khánh (Vietnam Journal of Chemistry, 2014)
For the acces to new pyrrolizines derivatives with potential biological interest, we implemented the Clauson-Kaas reaction using dimethoxytetrahydrofurane reagent on the 3-amino-3-arylpropanoic acids derivatives obtained during our work to give the pyrrolic compounds which were transformed into pyrrolizine derivatives by intramolecular cyclization